2008
DOI: 10.1021/pr070546l
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction, Oxidative Stress, and Apoptosis Revealed by Proteomic and Transcriptomic Analyses of the Striata in Two Mouse Models of Parkinson’s Disease

Abstract: The molecular mechanisms underlying the changes in the nigrostriatal pathway in Parkinson's disease (PD) are not completely understood. Here, we use mass spectrometry and microarrays to study the proteomic and transcriptomic changes in the striatum of two mouse models of PD, induced by the distinct neurotoxins 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and methamphetamine (METH). Proteomic analyses resulted in the identification and relative quantification of 912 proteins with two or more unique pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
89
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 55 publications
10
89
1
2
Order By: Relevance
“…Moreover, the experimental approach allowed for identifying the pathways activated specifically by these toxins. For instance, a more pronounced decrease in protein levels was observed in the MPTP mice than in the METH model [109]. The majority of the proteins identified in this study functionally associate with apoptosis, which is likely to be due to mitochondrial dysfunction and oxidative damage.…”
Section: Reviewmentioning
confidence: 64%
See 3 more Smart Citations
“…Moreover, the experimental approach allowed for identifying the pathways activated specifically by these toxins. For instance, a more pronounced decrease in protein levels was observed in the MPTP mice than in the METH model [109]. The majority of the proteins identified in this study functionally associate with apoptosis, which is likely to be due to mitochondrial dysfunction and oxidative damage.…”
Section: Reviewmentioning
confidence: 64%
“…In the study reported by Chin and colleagues, the downregulation of several anti-apoptotic and upregulation of pro-apoptotic genes and proteins were detected in both models [109]. For instance, the classic glycolytic protein glyceraldehyde-3-phosphate dehydrogenase, previously identified as a mediator of one or more apoptotic cascades and as a role-player in promoting LB formation [112], was found upregulated in both PD models.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Such a complex pattern of cell impairment makes proteomics one of the most useful tools to integrate these modifications into a whole systematic picture. The reports that recently appeared on the proteomic analysis of amyloid diseases such as Alzheimer's disease, Parkinson's disease and others have provided valuable data on some cell modifications allowing to explain, at least in part, cell impairment in these diseases [12][13][14][15][16]. Proteomic studies provided useful information on the changes in pattern of protein expression in cells exposed to toxic aggregates of specific peptides/proteins found aggregated in the corresponding diseases.…”
Section: Biochimica Et Biophysica Acta 1794 (2009) 1243-1250mentioning
confidence: 99%